British Medical Association and the National Health Service Bill (1946)
1946 1946 1940s 8 pages committee in close relation to, and represented upon, the committee of management. 16. On the subject of ownership, the Association recognizes that the Government's proposals raise serious issues which will be the concern of the public as a whole. The adoption of these proposals as they stand will inevitably involve a loss of local personal interest, and the discouragement of local support, whether in the form of contributions or of service. At present the local hospital, whether voluntary or council, commands a great deal of local pride, resource and initiative, amounting sometimes to individual sacrifice for the community's good. Somehow or other these things must be preserved. These arguments for the preservation of the individual character and the local relationships of hospitals are not mere sentimentality. They bear closely, for example, on the hospital's capacity for innovation and experiment, its power to attract nursing and other staff and the confidence of the local people in their local hospital. The Association has consistently pressed for an effective and appropriately constituted regional body with sufficient powers, financial and other, to secure the planned development of hospital services. In the Association's view, the Minister should accept responsibility for all hospital provision and maintenance, voluntary and council, being advised on the allocation of the necessary centrally provided monies by regional bodies. Such an arrangement would secure to the Minister and to the regional body all necessary power in the organization and development of the hospital service of its area, and it is unnecessary and undesirable for the Minister to proceed to assume actual ownership of hospitals, council or voluntary. 17. The Government's proposals might threaten private consulting practice despite the fact that the proposal of part-time service for some consultants is based on the assumption that private practice will be facilitated. The state, as owner of the hospitals, will control the private or semi-private accommodation and so will be free to convert private accommodation to semi-private accommodation and either to public accommodation when it so desires. In this way, and by its control of fees charged in private accommodation, it will control private consulting practice in so far as it is conducted in hospital premises. There will be scope for people to obtain additional amenities, e.g., private rooms where these are not medically necessary, by payment of the extra cost involved. But it appears that private accommodation will be restricted to particular hospitals where provision can be made "in separate parts of the hospital", and that the facilities will be limited to specialists taking part in the new service. This provision should not exclude the recognition of rooms and beds in the main hospital buildings as private accommodation. The Association is opposed to a restriction of the use of private accommodation of a particular hospital to specialists taking part in the new service. In the public interest the conditions imposed should not be such as would lead or compel consultants or their patients to use nursing home or similar accommodation dissociated from the hospitals for private consultation and treatment. Teaching Hospitals 18. The proposals for the administration of teaching hospitals can be judged only when fuller information as to the composition of the proposed boards of governors is known. It is not clear to what extent hospitals affording post-graduate clinical teaching and research will be regarded as teaching hospitals for the purpose of these arrangements. It is not clear what part the University Grants Committee will play in financing teaching hospitals. Only when fuller information is available can the proposals in relation to teaching hospitals be judged. LOCAL CLINIC, DOMICILIARY AND WELFARE SERVICES 19. The proposals under this heading have been the subject of comment in earlier paragraphs. The Association dislikes the proposals to place a statutory duty on local health authorities in respect of school medical and maternity and child welfare services, domiciliary midwifery, health visiting and home nursing services, vaccination and immunization, and a general ambulance service. Similarly, the Association is opposed to the proposal to place the responsibility for the provision and maintenance of health centres, dental centres and similar premises upon the local health authority. The health centre no less than the hospital should be the responsibility of the regional board. In the case of the ambulance service the case for regional organization is no less strong, for this, the committee believes, is the only way of bringing to an end the irritating limitations imposed by local authorities on the use of their ambulances outside their areas. These services should, in the Association's view, be administered, together with the hospital service, at the regional level. FAMILY PRACTITIONER SERVICES 20. An objective from the outset will be the development of the health centre system. The profession is deeply interested in health centres — indeed, the general idea was first put forward by the profession itself. But it would be contrary to the public interest to proceed to a rigid health centre policy without widespread experiment into the merits and demerits of different types of health centre in different types of area. The Association suggests an immediate experimental investigation, under medical guidance, of health centres of varied types and functions. Some advantages, such as the organization of nursing and 5 292/847/4/40